Sarcocystis moreliae sp. nov. in the imported green tree python Morelia cf. viridis (Reptilia, Pythonidae) - Máca, Ondřej; González-Solís, David (Frontiers in Veterinary Science, 2023)
Species of Sarcocystis use various vertebrates as intermediate or definitive hosts in their life cycles. One of these is snakes, whose role as intermediate hosts for these protozoans is scarce; in fact, there are six records, but only three with molecular characterization. An imported green tree python was involved in the morphological and molecular characterization (four loci) of a new species of Sarcocystis localized in skeletal muscles. Sarcocystis moreliae sp. nov. has a type 1 sarcocyst with a smooth wall and is genetically similar (at the 18S rRNA gene) to two unnamed species of Sarcocystis found in Lytorhynchus diadema from Oman and Varanus salvator macromaculatus from Malaysia, but their detailed comparison is impossible. The new species showed lower similarity to its congeners in other loci (28S rRNA, ITS1, and cox1). This is the first morphological and genetic characterization of a Sarcocystis species in snakes of the genus Morelia, particularly M. viridis, using four loci, but more data are needed to fill the knowledge gap about snakes as intermediate hosts of Sarcocystis.